Network dynamics in nanofilled polymers - Guilhem P. Baeza (Nature Portfolio, 2016)
The mixture of nanoparticles and polymers can dramatically alter the dynamics of the resulting system, but the detail is still under debate. Here, Baeza et al. show the formation of a percolated network by polymer bridging between adjacent nanoparticles as nanoparticle concentration increases.